2012
DOI: 10.1177/1049909112464544
|View full text |Cite
|
Sign up to set email alerts
|

Physician Attitudes Toward Advanced Directives

Abstract: The findings from this review are of importance in explaining the differences in the attitude of physicians toward AD and their compliance. This raises the issue of consideration of other ethical paradigms/theories in the clinical context other than the framework of "principlism-"based autonomy, on which AD leans on. This is important in light of the pluralism of ethical theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…In line with previous studies, the broad majority of the professionals asked found ADs helpful in knowing their patient’s will and ensuring the patients receive the care they really want [12, 13]. However, the enactment of the law did not have an effect on the physicians’ and nurses’ opinion, which could be seen as in accordance with the clarifying character of the legislation.…”
Section: Discussionsupporting
confidence: 77%
“…In line with previous studies, the broad majority of the professionals asked found ADs helpful in knowing their patient’s will and ensuring the patients receive the care they really want [12, 13]. However, the enactment of the law did not have an effect on the physicians’ and nurses’ opinion, which could be seen as in accordance with the clarifying character of the legislation.…”
Section: Discussionsupporting
confidence: 77%
“…7 , 8 Although most physicians demonstrate positive attitudes towards AD, the attending team does not always follow the plan of care established in the AD. 5 , 9 , 10…”
Section: Introductionmentioning
confidence: 99%
“…( 7 , 8 ) Apesar da maioria dos médicos demonstrar atitudes positivas em relação às DAV, nem sempre a equipe assistente segue o planejamento de cuidado determinado na DAV. ( 5 , 9 , 10 )…”
Section: Introductionunclassified
“…According to a cross-cultural survey study 12) of medical professionals and patients, the AD completion rates were 79% and 9% in the United States and Japan, respectively; when asked about the usefulness of AD in palliative care, 100% of the respondents in the United States indicated that AD were useful, compared to 71% of the respondents in Japan. In one study on the attitudes of medical professionals regarding AD, 13) the opinions of families were identified as important in the Asian countries of Japan, Thailand, and Singapore. This finding may be due to the cultural background of Asia in which family-centered decision-making has a large impact on the establishment of patient treatment plans.…”
Section: Discussionmentioning
confidence: 99%